MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION BERBASIS OBSERVASI GEJALA FISIS PADA PEMBELAJARAN IPA-FISIKA DI SMP - Tri Mardiyanti Rahayu; Sri Astutik; Trapsilo Prihandono (FKIP Universitas Jember, 2017)
The cooperative learning model type group investigation based on observations of physical symptoms is one model that can improve learning outcomes and developing science process skills of students in science subjects. This research aims to reviewing the difference in students learning outcomes that are taught using the cooperative learning model type group investigation based on observations of physical symptoms with the students taught using direct learning model that usually taught by a teacher in junior high school and describe the students learning science process skills after using the cooperative learning model type group investigation based on observations of physical symptom. This type of research is an experimental research conducted at the country junior high school 7 Jember. Source of data derived from the assessment by the observer, post-test, and filling the questionnaire. Based on the research that has been conducted, the obtained 1) t test assessment results obtained sig. 0.001 ≤0.05 so that Ha accepted and Ho rejected, it means there is a significant difference between the students taught by the cooperative learning model type group investigation based on observations of physical symptom with students taught using direct learning model commonly taught by teacher in junior high school 2) The avarage results of students learning science process skills in each indikator that is 90,33%. Means the learning science process skills of students while using the cooperative learning model type group investigation based on observations of physical symptom included in the category good